Education for all: Barriers and facilitators of inclusion in Higher Education - Araneda Gómez, Paula; Mancilla Rubio, Alicia; Sánchez León, Natalia; Pérez González, Carolina (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Inclusion in Chilean higher education has been framed within the context of respect for diversity, sustainability and dignity of people. The application of the Index for Inclusion at the Bernardo O’Higgins University installs as an exercise the self-assessment regarding the inclusive processes themselves. This quantitative research allows us to propose improvements from the reflection of the educational community itself regarding inclusive culture, policies and practices. Knowing the community, its needs and interests, respecting its potential independent of its diversity, is what allows us to establish learning and teaching processes that ensure education for all.